The Last Verse : A Novel. - Frost, Caroline (New York William Morrow, 2024)
When aspiring musician Twyla Finch arrives in Nashville, Tennessee, in 1977, a night out with Chet Wilton - a country music hopeful - goes terribly wrong. Hoping to process what happened that fateful night, she composes a haunting ballad that she performs only once in an empty bar. But weeks later, when she turns on the radio, she hears another woman singing her song. Twyla must decide whether to claim her ballad, securing the fame she's always wanted - but implicating her in the terrible crime she's desperate to put in the past. Author of "Shadows of Pecan Hollow." Print run 75,000.
new book 2024 spring.
10 57
Keywords: Country musicians -- Fiction; Women singers -- Fiction; Man-woman relationships; Songs; Ambition; Betrayal; Theft; Coming of age; Determination (Personality trait); Nashville (Tenn.) -- Fiction; Coming-of-age fiction; Thrillers; Thriller fiction; Historical fiction